Analisis Strategi Co-Working Dalam Peningkatan Penjualan - Rochma, Zakiyatul; Indriya Himawan, Abdurrahman Faris (Jurnal Mahasiswa Manajemen, 2023)
Background - With a lot of intense business competition nowadays, it hampers SMEs from increasing their sales. One of the obstacles faced by SMEs is their sales strategy to achieve success in their business. So that SMEs must know what strategies can increase their sales and in which areas can help develop their business. This is also experienced by UKM Felda Collection, therefore UKM Felda Collection decided to carry out a co-working strategy which is expected to have a major impact on increasing sales turnover of UKM Felda Collection. Objective - The purpose of this study was to analyze co-working strategies in increasing sales (case study on UKM Felda Collection). Design/Methodology/Approach - The type of research in this study is qualitative research. The selection of informants in this study was to conduct interviews with 3 (three) informants, namely the owners of UKM Felda Collection and employees of UKM Felda Collection, these informants were selected by purposive sampling with the criteria (1) mastering or understanding the Business Development of UKM Felda Collection (2) classified as still currently involved in or involved in the development process of UKM Felda Collection (3) knows and understands what is a co-working strategy (4) has free time to be asked for information. Data collection techniques used were observation, interviews, and documentation. Data analysis used data reduction, data presentation and conclusion drawing. Data validation techniques using membercheck and source triangulation. Findings - The results of this study indicate that UKM Felda Collection uses a co-working strategy in increasing sales turnover by joining the IWP community (association of women entrepreneurs) by participating in several activities in it, because this strategy has an important role in introducing and promoting products wide, so that it has a good impact on increasing the sales of SMEs Felda Collection and SMEs can also develop their business better in the face of very tight competition in this industry. Research implications - From the results of interviews with the three informants of the SME Felda Collection Gresik, the co-working strategy that has been used by the Felda Collection UKM has an effect and has a good impact in increasing sales of Felda Collection UKM products. Research limitations - This research was only conducted on SMEs that have used the co-working strategy and understand what the co-working strategy.